2017
DOI: 10.1007/s11274-017-2336-0
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of microbiota associated with symptomatic and non-symptomatic bacterial wilt-diseased banana plants determined using 16S rRNA metagenome sequencing

Abstract: Banana is one of the most important fruits cultivated in Malaysia, and it provides many health benefits. However, bacterial wilt disease, which attacks bananas, inflicts major losses on the banana industry in Malaysia. To understand the complex interactions of the microbiota of bacterial wilt-diseased banana plants, we first determined the bacterial communities residing in the pseudostems of infected (symptomatic) and diseased-free (non-symptomatic) banana plants. We characterized the associated microorganisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…Yet, microbiomics is waiting to be used in a more frequent way in the research field of banana, FWB, and biocontrol. Recent studies ( 16S rRNA and ITS amplicon sequencing profiling) have been focused on endophytic bacterial communities present in different parts and micro-environments of banana plants (Köberl et al, 2015, 2017; Zhai et al, 2016; Suhaimi et al, 2017), as well as in the microbiota of banana rhizosphere (Fu et al, 2016a) and soil (Xue et al, 2015; Rames et al, 2018).…”
Section: Fusarium Wilt Of Banana and The Banana-associated Microbiomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, microbiomics is waiting to be used in a more frequent way in the research field of banana, FWB, and biocontrol. Recent studies ( 16S rRNA and ITS amplicon sequencing profiling) have been focused on endophytic bacterial communities present in different parts and micro-environments of banana plants (Köberl et al, 2015, 2017; Zhai et al, 2016; Suhaimi et al, 2017), as well as in the microbiota of banana rhizosphere (Fu et al, 2016a) and soil (Xue et al, 2015; Rames et al, 2018).…”
Section: Fusarium Wilt Of Banana and The Banana-associated Microbiomesmentioning
confidence: 99%
“…Similarly, analyzing the banana/ R. solanacearum pathosystem (bacterial wilt of banana or Moko), five major microbial genera were found in both symptomatic and non-symptomatic plant samples: Sphingomonas, Methylobacterium, Flavobacterium, Pseudomonas , and Ralstonia , the latter being more abundant in symptomatic (59% out of the entire genera) than in non-symptomatic plants (only 36%). In addition, several genera were only assigned to non-symptomatic plants (Suhaimi et al, 2017). Another experiment showed that the soil cultivated with tobacco and infested by R. solanacearum had lower microbial diversity than the soil free from the pathogen, which harbored more abundant beneficial microbes such as Bacillus, Agromyces, Micromonospora, Pseudonocardia, Acremonium, Lysobacter, Mesorhizobium, Microvirga, Bradyrhizobium, Acremonium , and Chaetomium .…”
Section: Fusarium Wilt Of Banana and The Banana-associated Microbiomesmentioning
confidence: 99%
“…The eight samples (S1H, S2I, S3H, S4I, S5H, S6I, S7H, and S8I) were analyzed together with a QIIME suite of tools for a microbial analysis. A metagenomic analysis of the microbial community involves problems of plant DNA intrusion which adversely affect the analysis [20,21]. In the present study, we used a well-defined protocol to eliminate the intervention of banana host DNA that inhabits Fusarium symptomatic roots.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the olive cultivar seems to influence the establishment of pathobiome communities in olive knots. Accordingly, previous studies have suggested that differences on microbial abundance and diversity between asymptomatic and symptomatic tissues were possibly related to the susceptibility of the plant host to a certain disease 16,[18][19][20][21] . We hypothesized that the detected greater differences in the bacterial composition of OK-susceptible cv.…”
Section: Discussionmentioning
confidence: 99%